Long-term influence of trace element deficiency on anaerobic mono-digestion of chicken manure - ÇALLI, BARIŞ (ACADEMIC PRESS LTD- ELSEVIER SCIENCE LTD, 2018)
Recent findings showed that some trace elements essential for anaerobic digestion might be deficient in chicken (laying hens) manure. In this study, the long-term influence of trace element deficiency on anaerobic mono-digestion of chicken manure was investigated. Three bench-scale anaerobic reactors were operated with or without trace element supplementation. As trace element, only Se or a mix containing Co, Mo, Ni, Se, and W was added to the reactors. The results revealed that in anaerobic digestion of thicken manure at total ammonium nitrogen concentrations over 6000 mg L-1, Se supplementation was critical but not sufficient alone for long-term stable CH4 production. Addition of a mix consisting of Co, Mo, Ni, Se and W resulted in a more stable digestion performance. Daily trace element mix supplementation promoted the hydrogenotrophic Methanoculleus bourgensis, which is an ammonia tolerant methanogen. The decrease in the relative abundance of Methanoculleus detected after termination of trace element addition and resulted in accumulation of acetate and propionate that followed by a significant decrease in CH4 production.
Keywords: Ammonia; Methane; Selenium; Syntrophic acetate oxidation; Methanoculleus; BIOGAS PRODUCTION; POULTRY LITTER; AMMONIA INHIBITION; PROCESS STABILITY; LINKING PROCESS; FERMENTATION; METHANOGENS; PERFORMANCE; COCULTURE; COMMUNITY